Ericoid mycorrhizal symbiosis: theoretical background and methods for its comprehensive investigation - Vohník, Martin (Mycorrhiza, 2020)
Despite decades of intensive research (especially from 1970s to 1990s), the ericoid mycorrhizal (ErM) hair root is still largely terra incognita and this simplified guide is intended to revive and promote the study of its mycobiota. Basic theoretical knowledge on the ErM symbiosis is summarized, followed by practical advices on Ericaceae root sample collection and handling, microscopic observations and photo-documentation of root fungal colonization, mycobiont isolation, maintenance and identification and resynthesis experiments with ericoid plants. The necessity of a proper selection of the root material and its surface sterilization prior to mycobiont isolation is stressed, together with the need of including suitable control treatments in inoculation experiments. The culture-dependent approach employing plating of single short (~ 2 mm) hair root segments on nutrient media is substantiated as a useful tool for characterization of Ericaceae root-associated fungal communities; it targets living mycelium and provides metabolically active cultures that can be used in physiological experiments and taxonomic studies, thus providing essential reference material for culture-independent approaches. On the other hand, it is stressed that not every mycobiont isolated from an ericoid hair root necessarily represent an ErM fungus. Likewise, not every intracellular hyphal coil formed in the Ericaceae rhizodermis necessarily represents the ErM symbiosis. Taxonomy of the most important ericoid mycobionts is updated, mutualism in the ErM symbiosis is briefly discussed from the mycobiont perspective, and some interesting lines of possible future research are highlighted.
Keywords: symbióza; Mycorrhizae; rostliny; kořeny rostlin; Plant Roots; Plants; Plating of surface-sterilized root segments; Culture-dependent approach; Symbiosis; Ericoid mycorrhizal fungal diversity; Isolate identification; Microscopy; mykorhiza; In vitro resynthesis; Ericaceae; Mycobiont isolation